Typical Orbital Pathologies: Hemangioma - Low, Christopher M.; Stokken, Janalee K. (Journal of Neurological Surgery Part B: Skull Base, 2021)
Orbital hemangiomas are the most common primary neoplasm of the orbit and manifest as two distinct pathologic entities: infantile hemangiomas and cavernous hemangiomas. In this article, both infantile and cavernous hemangiomas are reviewed, with special attention paid to the natural history, clinical presentation, and management teams and approaches involved. An example case of each type of hemangioma is presented along with pearls and tips a reader can take away after reading this article.
Keywords: orbital hemangioma; orbital infantile hemangioma; orbital cavernous hemangioma; orbital cavernous vascular malformation; orbital pathology; orbital tumor